2021
DOI: 10.1088/1755-1315/802/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Removal of ammonia in domestic wastewater by using multi soil layering

Abstract: Domestic wastewater is the primary source of river pollution. Every human activity in the house must produce waste. Domestic wastewater from the kitchen, bathing, and washing activities contains organic pollutants. The parameter tested was ammonia. In this study, Multi Soil Layering (MSL) was used as a processing method. This treatment serves to reduce ammonia levels in wastewater. This study aims to determine the removal of ammonia in greywater using the Multi Soil Layering System. Wastewater samples were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…The achieved good reduction of NH 3 concentrations from the investigated grey wastewater using treatment system type (A) might indicate a good adsorption capacity of the rice straw in addition to the sand and gravel media. The results of the current study revealed a high removal efficiency of NH 3 using treatment systems (A, B and D) in comparison with the results indicated by Wardani et al (2021), who demonstrated that the removal rates of NH 3 after utilizing a multi soil layering method by three reactors' relative to treat household wastewater with a percent removal of 49 and 51%.…”
Section: Tds and Ec Values Of The Four Treatment Systemssupporting
confidence: 56%
“…The achieved good reduction of NH 3 concentrations from the investigated grey wastewater using treatment system type (A) might indicate a good adsorption capacity of the rice straw in addition to the sand and gravel media. The results of the current study revealed a high removal efficiency of NH 3 using treatment systems (A, B and D) in comparison with the results indicated by Wardani et al (2021), who demonstrated that the removal rates of NH 3 after utilizing a multi soil layering method by three reactors' relative to treat household wastewater with a percent removal of 49 and 51%.…”
Section: Tds and Ec Values Of The Four Treatment Systemssupporting
confidence: 56%
“…Ammonia is a commonly found pollutant in wastewater, and its presence exceeding the discharge limits can have adverse impacts on aquatic ecosystems. It can result in heightened toxicity, imbalances in nutrients, and potential harm to aquatic organisms [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 shows the average range of the ammonia parameters for the untreated and treated greywater samples using different wetland technologies as observed, they range from 1.9 ± 0 (mg/L), 1.6 ± 0.1773 (mg/L), 1.7 ± 0.1553 (mg/L), 1.8 ± 0.0916 (mg/L), and 1.9 ± 0.034 (mg/L) for HSFS-CWT, VSSF-CWT, VFSF-CWT, and HSSF-CWT, respectively. Greywater ammonia is produced from the decomposition of organic kitchen waste [ 22 ]. The ammonia concentration in greywater samples is low, although the ammonia removal efficiency varied among different wetland technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini didukung dengan adanya adsorpsi dari karbon aktif dan zeolit. Zeolit memiliki kemampuan adsorpsi dan pertukaran ion pada penyisihan amonia dengan mengubah amonia menjadi nitrat 25 .…”
Section: Hasil Penyisihan Konsentrasi Amonia Setelah Filtrasiunclassified